THE DEVELOPMENT OF MULTIPLE EPRESENTATIONS BASED STUDENT WORKSHEET TO IMPROVE LEARNING RESULTS OF GRADE V ELEMENTARY SCHOOL STUDENTS - Akramida, Hidari; Distrik, I Wayan; Suntoro, Irawan (International Journal of Research -GRANTHAALAYAH, 2020)
The objective of this research was to develop Multiple Representations based student worksheet to improve elementary school learners’ learning results in Way Kanan district, Lampung province, Indonesia. This research used Research and Development (R & D) method by following steps made by Borg & Gall, which were simplified into three stages; preliminary study, planning and development, and field test. It used static group pretest-posttest design. Population was grade V elementary school learners in Way Kanan district, Lampung, Indonesia. Samples were two classrooms of grade V elementary school learners and taken by using purposive random sampling. Data were collected with papers, test pencils, observation sheets and questionnaires. Data were analyzed by using descriptive and inferential analyses by using paired t-test. The research results showed that: 1) multiple representation based student worksheet theoretically valid shown by content validity by average of 92.37 out of 100 maximum score and construct validity by average of 91.02 and they belonged to very valid category; 2) multiple representation based student worksheet was practical and effective to use by grade V elementary school learners and this was shown by average of learners’ learning result averages by 75.00 in experiment classroom and 60.00 in control classroom.